THE ROLE OF VIDEO FEATURES AS A MEANS OF PROMOTING TOURISM VILLAGES AND DRIVING THE COMMUNITY'S ECONOMY - Azzahrah, Sintya Sativa; Koswara, Iwan; Subekti, Priyo (Universitas Mercu Buana, 2025)
This research aims to explore and reveal the role of video features in promoting Cimindi Tourism Village in order to increase the frequency of tourist visits and support the economic growth of the community. The method used in this research is a case study with a descriptive qualitative approach. Data were collected through content analysis of 10 videos, in-depth interviews with 17 informants, and direct observation of the economic impact for six months. The results imply that video features are able to increase the frequency of tourist visits by 68% and all visual content featuring the uniqueness of nature (Ciwayang Body Rafting), culture (Badud Art), and culinary (Nasi Liwet Jolem) are the main factors of success. Tangible economic impacts were seen in the increase in turnover of handicraft MSMEs (45%), homestay occupancy (30%), and the expansion of local product markets to the five new districts. This study proves that video features are not only effective promotional tools, but also economic catalysts based on community participation. The implications of the study recommend a hybrid model between professional production and user-generated content, as well as digital literacy training for tourist village managers. The findings offer a strategic framework for sustainable tourism development by integrating technology and local wisdom.